2021
DOI: 10.1038/s41598-021-01361-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating severe fever with thrombocytopenia syndrome transmission using machine learning methods in South Korea

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease in China, Japan, and Korea. This study aimed to estimate the monthly SFTS occurrence and the monthly number of SFTS cases in the geographical area in Korea using epidemiological data including demographic, geographic, and meteorological factors. Important features were chosen through univariate feature selection. Two models using machine learning methods were analyzed: the classification model in machine learning (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This understanding can not only provide key information for early monitoring and prevention of the epidemic, but also guide the formulation of public health policies, in order to establish a more sensitive disease monitoring system and emergency response mechanisms on a global scale. Previously, data on human infections were mostly published at the level of individual countries, 5 , 15 , 18 , 19 and data comparisons from a global perspective were only updated until 2018. 20 , 21 Further updates are needed on the reporting status of SFTS in human.…”
Section: Introductionmentioning
confidence: 99%
“…This understanding can not only provide key information for early monitoring and prevention of the epidemic, but also guide the formulation of public health policies, in order to establish a more sensitive disease monitoring system and emergency response mechanisms on a global scale. Previously, data on human infections were mostly published at the level of individual countries, 5 , 15 , 18 , 19 and data comparisons from a global perspective were only updated until 2018. 20 , 21 Further updates are needed on the reporting status of SFTS in human.…”
Section: Introductionmentioning
confidence: 99%
“…The BTR ML model from the modified RMML was superior to all others. The AUC for the BTR model was >0.9 at predicting the occurrence of SFTS [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mainly focused on multivariate analysis methods to predict the incidence of SFTS. These studies analyzed various environmental, meteorological, and social factors, among others, to identify incidence-related risk factors and establish prediction models based on these factors ( Cho et al., 2021 ; Deng et al., 2022 ; Ding et al., 2014 ; Sun et al., 2018 , 2021 ; Wu et al., 2020 ). However, few studies have reported models for prediction of SFTS incidence just based on the historical incidence data, which may be more convenient and practical.…”
Section: Introductionmentioning
confidence: 99%